Editorial: Emerging roles of circular RNAs in the tumor: functions and potential applications–volume II - Guo, Shanchun; Huang, Lan; Liu, Mingli (Frontiers in Cell and Developmental Biology, 2024)
Circular RNA (circRNA) has attracted substantial attention in the field of biological research. The surge in interest has led to a collective understanding of circRNA's pivotal roles in physiological development and various diseases (1-5). Recent use of RNA sequencing and bioinformatics methods has discovered a huge number of circRNAs in diverse cell lines and species. Emerging research suggests that many circRNAs exhibit cell-type specific expression and act as either oncogenic triggers or tumor suppressors in the context of cancer [6]. CircRNAs often display distinct expression patterns linked to specific tissues and cancer types. Notably, CircRNAs hold great promise as diagnostic, prognostic, and predictive biomarkers, as they are detectable in liquid biopsy samples (7-9). In a noteworthy development, synthetic circRNAs have been generated to explore their potential as a novel class of mRNA treatments and vaccines [10]. Recent research findings have shown that some cytoplasmic circRNAs can undergo translation, resulting in detectable peptides, thereby shedding light on the role of circRNAs in cancer biology [11]. Despite the inherent challenges associated with detecting, quantifying, and functionally characterizing circRNAs due to their unique nature, recent advancements in high-throughput RNA sequencing and the development of circRNA computational tools have facilitated the creation of cutting-edge methodologies for their identification. The research topic "Emerging Roles of Circular RNAs in the Tumor: Functions and Potential Applications-Volume II" focuses on circRNAs' role and molecular signaling pathways by which they regulate tumor development. We have received numerous manuscripts and finally selected 4 articles in cancer research.